Roles, reglas y límites de las familias extendidas y nucleares asociadas al cosumo de alcohol y drogas en los adolescentes del Primer Año de Bachillerato del Colegio Nacional Adolfo Valarezo de la ciudad de Loja. Periodo 2014-2015 - León Herrera, Gabriela del Cisne (2015)
In the following study it was intended to determine the incidence of roles and limits in extended and nuclear families associated with the consumption of alcohol and drugs in adolescents of the first year of baccalaureate from “Adolfo Valarezo” National High School in the town of Loja; for it was first scheduled to determine the family typology (nuclear and extended) of students investigated of the first year of baccalaureate from “Adolfo Valarezo” National School in the town of Loja and thus evaluate roles, rules and limits in extended and nuclear families in adolescents of the first year of baccalaureate from “Adolfo Valarezo” National High School in the town of Loja; to identify the consumption of alcohol and drugs and type of intervention required, with the purpose of contrast these problems of alcohol and drugs influenced by roles, rules and limits among adolescents belonging to extended and nuclear families; this is an analytical cross sectional study with a mixed quantitative-qualitative approach, which handled scientific methods such inductive-deductive and comparative, based on the use of techniques such a demographic survey and psychological reagents, such as TEST FASES III and ASSIST V3.0, through which it was evident that in both types there imbalance in the roles, rules and limits as well as the existence of alcohol and drugs in 90% of students surveyed, requiring brief intervention, and in some cases intensive treatment. Generally the adolescents of extended or nuclear families show consumption. The most commonly used substances are alcohol and snuff. The extended families have a higher prevalence of consumption preceded by imbalance in family functioning. Therefore direct involvement of managers is recommended as well as the commitment of parents and teenagers to undergo a psychological treatment for the overall improvement of the family. Keywords: Extended and nuclear families, adolescence, consumption, imbalance.